2016
DOI: 10.1185/03007995.2016.1140029
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (52 weeks) safety and tolerability of umeclidinium in Japanese patients with chronic obstructive pulmonary disease

Abstract: Objective Umeclidinium bromide (UMEC) 62.5 μg is a long-acting muscarinic antagonist (LAMA) that is administered once daily via inhalation for chronic obstructive pulmonary disease (COPD) treatment. The objective of this study was to evaluate the safety and tolerability of long-term treatment with UMEC 125 μg in Japanese patients with COPD. Methods This was a 52 week, multicenter, open-label study to evaluate the safety and tolerability of UMEC 125 μg once daily delivered via a novel dry powder inhaler (nDPI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Severe adverse events during the treatment period were reported in nine patients (7%) but none were considered to be drugrelated. Increased blood bilirubin was recognized in one patient due to UMEC 6 . UMEC is a substrate of cytochrome P450 2D6 and it is mainly metabolized in the liver.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Severe adverse events during the treatment period were reported in nine patients (7%) but none were considered to be drugrelated. Increased blood bilirubin was recognized in one patient due to UMEC 6 . UMEC is a substrate of cytochrome P450 2D6 and it is mainly metabolized in the liver.…”
mentioning
confidence: 93%
“…Both aclidinium and umeclidinium can be used in renal impairment 1 . Yamagata et al 6 reported a dropout rate of 15%, an expected percentage in a fragile population for a trial of 52 weeks' duration. The main causes of withdrawal were exacerbations and pneumonia, consistent with previous studies 1 .…”
mentioning
confidence: 99%
See 3 more Smart Citations